The Splenic Marginal Zone in Children Is Characterized by a Subpopulation of CD27-Negative, Lowly IGHV-Mutated B Cells - Kibler, Artur; Budeus, Bettina; Küppers, Ralf; Seifert, Marc (Frontiers in Immunology, 2022)
Young children and elderly humans suffer from enhanced susceptibility to infections with blood-borne pathogens. An essential step towards immunity is the establishment of a splenic marginal zone (sMZ), which is immature below two years of age. Around five years of age, an adult level of protection is reached but waning again in the elderly. Whereas the infant sMZ is thought to contain mostly naïve B cells, memory B cells are recruited to and recirculate from the sMZ throughout life, and class-switched sMZ B cells dominate in the elderly. For a better resolution of naïve versus memory B cell subset accumulation in the sMZ, we performed a single-cell based gene expression analysis of (CD21highIgMhigh) sMZ B cells among five healthy donors (age 3y to 48y) and validated the sMZ B cell subset composition by flow cytometry of 147 spleen biopsies (age 0y to 82y). We identified a major sMZ B cell subpopulation, which is abundant at birth but decreases with age. These cells lack CD27 expression but carry a weak to intermediate memory B cell signature. These CD27neg sMZ B cells are either IGHV-unmutated or carry only few IGHV mutations early in life but show average memory B cell IGHV mutation frequencies (>3%) in adults. The activation- and proliferation-potential of CD27neg sMZ B cells is significantly above that of non-sMZ B cells, already in children. Our study suggests that the human sMZ B cell pool changes with age, encompassing a major population of lowly Ig-mutated CD27neg but antigen-experienced B cells early in life.